2009
DOI: 10.1126/science.1176985
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide (N 2 O): The Dominant Ozone-Depleting Substance Emitted in the 21st Century

Abstract: By comparing the ozone depletion potential-weighted anthropogenic emissions of N2O with those of other ozone-depleting substances, we show that N2O emission currently is the single most important ozone-depleting emission and is expected to remain the largest throughout the 21st century. N2O is unregulated by the Montreal Protocol. Limiting future N2O emissions would enhance the recovery of the ozone layer from its depleted state and would also reduce the anthropogenic forcing of the climate system, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
2,186
3
42

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,849 publications
(2,359 citation statements)
references
References 14 publications
24
2,186
3
42
Order By: Relevance
“…The results were similar to those reported by Smil (2001), who found that only approximately half of all N that was applied to cropland as fertilizer is actually recovered in the harvested crops. Excessive use of nitrogenous fertilizer causes eutrophication, loss of diversity, dominance by weedy species, air pollution, water pollution, soil acidification, and emission of the ozone-depleting greenhouse gas nitrous oxide (Ravishankara et al, 2009). Ju et al (2009 also reported that on the North China Plain, 22%-40% of the N applied in wheat-maize rotation systems could be emitted via ammonia (NH 3 ) volatilization, nitrate leaching, and denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar to those reported by Smil (2001), who found that only approximately half of all N that was applied to cropland as fertilizer is actually recovered in the harvested crops. Excessive use of nitrogenous fertilizer causes eutrophication, loss of diversity, dominance by weedy species, air pollution, water pollution, soil acidification, and emission of the ozone-depleting greenhouse gas nitrous oxide (Ravishankara et al, 2009). Ju et al (2009 also reported that on the North China Plain, 22%-40% of the N applied in wheat-maize rotation systems could be emitted via ammonia (NH 3 ) volatilization, nitrate leaching, and denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Emissions of other anthropogenic ozone-depleting substances, for example, chlorine-and bromine-containing halocarbons, are steadily declining and have dropped significantly since the 1980s, whereas the levels of N 2 O emission are more stable (IPCC, 2007;Ravishankara et al, 2009). Today, N 2 O is the single most important substance among anthropogenic ozone-depletion emissions and will dominate in the future as ozone-depleting halocarbons are exhausted (Ravishankara et al, 2009). N 2 O is rarely included in assessments of the ozone-depletion potential in LCA, but the importance of considering N 2 O has been recognized (Lane and Lant, 2012).…”
Section: Nitrous Oxidementioning
confidence: 99%
“…Major losses of nitrogen (N) occur in these systems via ammonia (NH 3 ), nitrous oxide (N 2 O) and di-nitrogen (N 2 ) emissions to air, nitrate (NO 3 2 ) leaching to groundwater and via overland flow and discharges of particulate N to surface waters (de Klein et al, 2010). N 2 O contributes to losses of ozone in the stratosphere (Ravishankara et al, 2009) and it is the third most important greenhouse gas (GHG), with a global warming potential 298 times that of carbon dioxide (CO 2 ) over a 100-year time horizon. It is an obligate intermediate in denitrification, and is also produced during nitrifier denitrification and nitrification processes (Wrage et al, 2001).…”
Section: Introductionmentioning
confidence: 99%